2006
DOI: 10.1002/pmic.200500821
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic analysis of a meningococcal outer membrane vesicle vaccine prepared from the group B strain NZ98/254

Abstract: In the absence of a suitable carbohydrate-based vaccine, outer membrane vesicle (OMV) vaccines have been used to disrupt outbreaks of serogroup B meningococcal disease for more than 20 years. Proteomic technology provides physical methods with the potential to assess the composition and consistency of these complex vaccines. 2-DE, combined with MS, were used to generate a proteome map of an OMV vaccine, developed to disrupt a long-running outbreak of group B disease in New Zealand. Seventy four spots from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 74 publications
2
50
0
Order By: Relevance
“…The inactivated BVD vaccine A contained over 3.5 fold more proteins than the live-attenuated vaccine B and still over twice as many compared to a meningococcal vaccine , where 47 proteins were identified by similar proteomic approaches [22]. Total protein quantity of vaccine A and MDBK cells was almost equal, underlining our findings that the protein content of vaccine A and the host cell line surface resemble each other (Figure 1C and D).…”
Section: Discussionsupporting
confidence: 58%
“…The inactivated BVD vaccine A contained over 3.5 fold more proteins than the live-attenuated vaccine B and still over twice as many compared to a meningococcal vaccine , where 47 proteins were identified by similar proteomic approaches [22]. Total protein quantity of vaccine A and MDBK cells was almost equal, underlining our findings that the protein content of vaccine A and the host cell line surface resemble each other (Figure 1C and D).…”
Section: Discussionsupporting
confidence: 58%
“…EF-Tu was found in OM fractions of A. baumannii [24]. It also was present in OMVs of N. meningitides [38, 39] and E. coli [40]. However, a former proteomic analysis did not detect EF-Tu in the A. baumannii OMV fraction [25].…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, proteome analysis has demonstrated that EF-Tu is an immunogen that elicits antibody response during infection by several bacteria. 30,32,33 …”
Section: Introductionmentioning
confidence: 99%